Dating Violence in an Urban Turkish Context: Listening to Young People from an Intersectional Perspective - Ustunel, Anil Ozge (Journal of interpersonal violence, 2022)
Intersectional approaches have challenged the field of domestic violence to pay more attention to diversity in women?s experiences and highlighted the significance of their social contexts and positions, such as class, race, religion, in shaping their understanding of and responses to violence. In the dating violence (DV) literature, a similar call has been made to develop contextualized accounts of DV and to address the heterogeneity of young people through DV prevention programs. Nevertheless, to date, intersectional thinking has not been fully utilized in DV research. The present study aims to address this gap in the literature and investigate how young people make sense of and experience DV from an intersectional perspective in an urban Turkish context. The data for the current study came from individual interviews conducted with 39 college students, aged 18?25. The interviews inquired into how young people understood, explained, and experienced DV. The interviews were analyzed thematically, culminating into four main themes: (a) DV as control, (b) DV as resulting from traditional gender norms, (c) DV as women?s fault, and (d) DV-related socialization processes. Some of these main themes were interpreted and experienced differently by the participants depending on their gender and the impact of traditional, Islamic, and egalitarian discourses on their accounts. The result demonstrated nuanced differences in young people?s meaning-making perspectives, needs, and vulnerabilities to DV. In the Turkish context, these results are intended to inform the burgeoning field of DV research and to guide the development of diversity-informed, culturally tailored, and context-sensitive prevention practices.